Synthesis of 3,5-Disubstituted Anilines via Sequential Mo-Catalyzed Deoxygenative Benzene Formation and Pd-Catalyzed Amination Reactions - Fang, Gang; Yu, Yi-Zhe; Zhuo, Chun-Xiang (Synthesis, 2025)
The substituted anilines play a pivotal role as structural motifs in agrochemicals, organic polymers, and pharmaceuticals, and great efforts have been dedicated to advancing their synthesis. However, the highly efficient and selective synthesis of meta,meta-disubstituted anilines remains a challenge. Here, the synthesis of meta,meta-disubstituted anilines via sequential Mo-catalyzed deoxygenative benzene formation and Pd-catalyzed amination reactions is reported. By employing this method, a wide range of meta,meta-disubstituted anilines were accessed with up to 89% yield from readily accessible ynones, allylic amines, and amines.
Keywords: molybdenum catalysis; palladium catalysis; deoxygenative benzene formation; C–N bond cross coupling; 3,5-disubstituted anilines